Identification of cohesive crack fracture parameters using mathematical programming - Que, Norbert S.
This thesis is concerned with the characterization of the parameters governing the tension-softening relations of the cohesive crack model. Parameters identification is an important area in fracture mechanics as it enables the use of a fracture model for the simulation of fracture processes in structure. Research, however, has shown that such a task is not trivial and continues to pose challenging problems to experimentalists and analysts alike. This dissertation presents general and efficient indirect methods for the characterization of mode I fracture parameters defining the cohesive crack model.